2014
DOI: 10.1155/2014/439501
|View full text |Cite
|
Sign up to set email alerts
|

EarlyTrypanosoma cruziInfection Reprograms Human Epithelial Cells

Abstract: Trypanosoma cruzi, the causative agent of Chagas disease, has the peculiarity, when compared with other intracellular parasites, that it is able to invade almost any type of cell. This property makes Chagas a complex parasitic disease in terms of prophylaxis and therapeutics. The identification of key host cellular factors that play a role in the T. cruzi invasion is important for the understanding of disease pathogenesis. In Chagas disease, most of the focus is on the response of macrophages and cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 48 publications
2
39
0
1
Order By: Relevance
“…Although Castillo et al (2018) previously reported changes similar to those described in the present model, the number of downregulated genes was high compared with that observed by Chiribao et al (2014). That study found a high number of differentially expressed genes (1700) when the effect of infection on epithelial cells was analyzed.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although Castillo et al (2018) previously reported changes similar to those described in the present model, the number of downregulated genes was high compared with that observed by Chiribao et al (2014). That study found a high number of differentially expressed genes (1700) when the effect of infection on epithelial cells was analyzed.…”
Section: Discussionsupporting
confidence: 58%
“…Undoubtedly, T. cruzi infection produces significant changes in cellular gene expression, as shown in several reports (Manque et al, 2011; Chiribao et al, 2014; Li et al, 2016). These findings were also observed in our model, where 159 genes were upregulated and 242 were downregulated during the infection.…”
Section: Discussionmentioning
confidence: 82%
“…Although disease pathogenesis remains unclear, it is well known that both parasite and host responses play relevant roles. Immediately after adhesion and during the initial stages of infection, Trypanosoma cruzi dramatically remodels host cell gene expression profile, with specific patterns on each cell type ( 1 , 2 ); B and T cell immunity also plays important roles both in the control and pathogenesis of the disease ( 3 , 4 ). The low or null parasite cardiac load in patients with chronic chagasic cardiomyopathy lead a discussion in the literature regarding the etiology of Chagas disease, where different factors such as T. cruzi strains, genetic background of the host, altered immune responses, and autoimmunity where associated with clinical outcomes of the disease [reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the parasite load and leucocytes infiltrate, our results also indicated that animals treated with the highest doses of Sur exhibited high cardiac levels of TNF- α and IFN- γ , which are two effector molecules produced from the polarized Th1 immunological phenotype [ 43 , 44 ]. In addition to the direct leucocyte recruitment triggered by cytokines (e.g., TNF- α , IFN- γ ) and chemokines (e.g., MCP1, MIP-1 and 2) secreted in response to T. cruzi antigens, direct cardiomyocytolysis, and cell death induced by the continuous replication of amastigotes also contributes to leucocyte recruitment and activation [ 45 , 46 ]. There is evidence that high parasite load is closely correlated with intense immunological polarization to a Th1 phenotype, which is paradoxically implicated in antitrypanosomal defense and cardiac damage [ 19 , 26 , 44 ].…”
Section: Discussionmentioning
confidence: 99%